2000
DOI: 10.1074/jbc.m006639200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Mitochondrial Copper Metallochaperone Cox17

Abstract: The copper metallochaperone Cox17 is proposed to shuttle Cu(I) ions to the mitochondrion for the assembly of cytochrome c oxidase. The Cu(I) ions are liganded by cysteinyl thiolates. Mutational analysis on the yeast Cox17 reveals three of the seven cysteinyl residues to be critical for Cox17 function, and these three residues are present in a Cys-Cys-Xaa-Cys sequence motif. Single substitution of any of these three cysteines with serines results in a nonfunctional cytochrome oxidase complex. Cells harboring su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
111
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 28 publications
9
111
1
1
Order By: Relevance
“…First, endogenous PKA was detected in the outer membrane and inner membrane space of highly purified, fractionated mitochondria. 4 Second, upon stimulation of HeLa cells with CPT-cAMP, an increase in phospho-ChChd3 Thr 10 is detected in intact mitochondria by confocal microscopy. 5 There are many different protein kinases in the cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, endogenous PKA was detected in the outer membrane and inner membrane space of highly purified, fractionated mitochondria. 4 Second, upon stimulation of HeLa cells with CPT-cAMP, an increase in phospho-ChChd3 Thr 10 is detected in intact mitochondria by confocal microscopy. 5 There are many different protein kinases in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal antisera to full-length ChChd3 were generated in rabbits against the peptide sequence QAKKESEHQRRLKQARDLERER (Invitrogen). Affinity-purified polyclonal antibodies to phosphoChChd3 Thr 10 were generated in rabbits against an N-terminal peptide RRVT(PO 3 )FEADENENC (Pacific Immunology Corp, Ramona, CA).…”
Section: Two-dimensional Electrophoresis/maldi-tof-proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of Cox17, Sco1, and Cox11 in copper metallation of CcO were substantiated by the observation that each protein is a Cu(I)-binding protein and that mutations that abrogate in vivo function attenuate Cu(I) binding (11,(13)(14)(15). Cox17 is a soluble protein that localizes within the IMS and also within the cytoplasm (8).…”
mentioning
confidence: 99%
“…Cox17 is found in both the cytosol and mitochondria. It was originally thought that Cox 17 binds copper in the cytosol, translocates into mitochondria and delivers copper to Cox1 and Cox2 [48][49][50]. However, further studies in yeast showed that in Cox 17 deficient cells, CcO activity can be fully restored by mitochondrial restricted expression of Cox17 [51].…”
Section: Copper Metabolism In Eukaryotic Cellsmentioning
confidence: 99%